2002
DOI: 10.1016/s0375-9601(02)00277-3
|View full text |Cite
|
Sign up to set email alerts
|

Reply to “Comments on Bouda and Djama's ‘Quantum Newton's Law’”

Abstract: In this reply, we hope to bring clarifications about the reservations expressed by Floyd in his comments, give further explanations about the choice of the approach and show that our fundamental result can be reproduced by other ways. We also establish that Floyd's trajectories manifest some ambiguities related to the mathematical choice of the couple of solutions of Schrödinger's equation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 7 publications
(28 reference statements)
0
33
0
Order By: Relevance
“…It can also be obtained by applying (8) or (11). As expected, it is a fourth order differential equation.…”
Section: The Quantum Law Of Motionmentioning
confidence: 80%
See 1 more Smart Citation
“…It can also be obtained by applying (8) or (11). As expected, it is a fourth order differential equation.…”
Section: The Quantum Law Of Motionmentioning
confidence: 80%
“…In Ref. [11], it is shown that the resulting trajectories depend on the choice of the couple of solutions of the SE used in the expression of S 0 . This represents an unsatisfactory feature since the mathematical choices affect the physical results.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular hydrogen and carbon dioxide have been chosen as benchmarking systems for fundamental studies as well as for medical applications. Particular attention is given to the emission characteristics of the low-energy electrons, which are very reactive in biological tissue [1].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, many suggestions to formulate the quantum trajectory equations were proposed [3,4,15,17,18,19,20]. In a recent paper [21], the QSHJE in one dimension, 1 2m…”
Section: Introductionmentioning
confidence: 99%